Potencial del rastrojo de maíz con leguminosa en la alimentación de ganado de engorde - Sinclair G., Rubén; Wege, Linus; Romero, Andrés (Agronomía Mesoamericana, 2016)
An assay was conducted to test the value of traditional and legume improved stubbles when fed to beef steers, in Aramis, Olancho, Honduras (dry tropical forest). A complete randomized block experimental design was used, with an area of 5000 m2 for each model, weaned cross-bred (brahman x creole) steers with an average weight of 150 kg and the legume Lablab purpureus planted at the coro hiUing. The four treatments evaluated were: 1. Grazing on the traditional stubble, 2. Grazing on the improved stubble, 3. harvested traditional stubble (confinement) and 4. Harvested improved stabble confinementThe weight gain was significant (P< =0,01) among treatments. The highest weight gain of 1019 g/animal/day was obtained with the group that grazed on improved stubble and the lowest gain (548.1 g/day) with the harvested traditional stubble. The animal/ha weight gain, adjusted at 6 weeks of roughage management, showed superiority of the improved stubbles (5.8 and 2.9 kg/ha/day, respectively).